A Spiral in the Heart: Mitral Valve Endocarditis with Unusual Vegetation Shape Potentially Affecting Effectiveness of Antibiotic Therapy - Veronica Fibbi; Piercarlo Ballo; Alessandro Abbondanti; Marco Nannini; Antonio Fazi (Case Reports in Cardiology)
We report an unusual case of infective endocarditis (IE) in an 88-year-old woman, occurring on a prolapsing mitral valve and characterized by an atypical vegetation shape resembling a spiral-like appearance. After the patient refused surgical correction, persistent IE despite prolonged antibiotic therapy was observed, resulting in an ischemic stroke probably secondary to septic embolus. The importance of vegetation shape in the management of patients with IE was classically related to the increased risk of embolization associated with pedunculated, irregular, and multilobed masses. We hypothesize that the unusual spiral-like vegetation shape in our patient may have favored IE persistence by two mechanisms, namely, a decrease of the exposed vegetation surface with creation of an internal core where the penetration of antimicrobial agents was obstacled and the creation of blood turbulence within the vegetation preventing a prolonged contact with circulating antibiotics. These considerations suggest that vegetation shape might be considered of importance in patients with IE not only because of its classical association with embolization risk, but also because of its potential effect on the efficacy of antibiotic therapy.